2000
DOI: 10.1007/s002040000137
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel in vitro system for studying the interaction of xenobiotic metabolism of liver and intestinal microflora

Abstract: We developed a new two-chamber system for the coculture of hepatocytes and fecal microflora under aerobic and anaerobic conditions, respectively, to investigate the sequential metabolism of chemicals by the liver and microflora in vitro. The culture device consisted of two chambers separated by a permeable polycarbonate membrane. In the aerobic compartment, hepatocytes were cultivated as a monolayer on the membrane and in the anaerobic compartment fecal microflora as a suspension. To characterize the metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Certain bacteria, such as Bacteroides species, appear to enhance mutagenicity via potent carcinogens, such as HCA, through these mechanisms. Additionally, exchanges between the liver and the intestine takes place through the enterohepatic circulation [80].…”
Section: Modulation Of Xenobiotic Metabolising Enzymesmentioning
confidence: 99%
“…Certain bacteria, such as Bacteroides species, appear to enhance mutagenicity via potent carcinogens, such as HCA, through these mechanisms. Additionally, exchanges between the liver and the intestine takes place through the enterohepatic circulation [80].…”
Section: Modulation Of Xenobiotic Metabolising Enzymesmentioning
confidence: 99%
“…This could be achieved, for instance, by means of separate compartmentalization of bacteria and cell lines, to avoid direct contact but allowing exchange of metabolites and signals between the two compartments. This appears to be a feasible approach as it is based on the typical structure of a microbial fuel cell (Pham et al 2009), with the presence of a permeable membrane, as shown by Laube et al (2000), who developed an in vitro system for studying the interaction of xenobiotic metabolism of liver and intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For most xenobiotics, including drugs and toxicants, the role of the intestinal microflora in metabolism has not been considered to be part of their mode of action. The interactions of hepatic drug‐metabolising enzymes and the intestinal microflora should be investigated to understand the metabolic fate of xenobiotics that undergo enterohepatic circulation. To accomplish this goal, novel in vitro systems that model the interactions of the liver with xenobiotic metabolism by the intestinal microflora and/or the interaction of the intestinal microflora with host transporters should be developed .…”
Section: Future Directions and Conclusionmentioning
confidence: 99%